Seasonality and scenario dependence of rapid Arctic sea ice loss events in CMIP6 simulations - A. Sticker; F. Massonnet; T. Fichefet; P. DeRepentigny; A. Jahn; A. Jahn; D. Docquier; C. Wyburn-Powell; C. Wyburn-Powell; D. Quint; E. Shivers; M. Ortiz (The Cryosphere)
The end-of-summer Arctic Ocean is projected to face at least one occurrence of practically ice-free conditions (sea ice extent <1×106<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="853d4a4e5483c299b6fba429ad84db0b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-19-3259-2025-ie00001.svg" width="46pt" height="14pt" src="tc-19-3259-2025-ie00001.png"/></svg:svg> km2) by the middle of the century under all Coupled Model Intercomparison Project Phase 6 (CMIP6) scenarios. Climate models indicate that this transition toward a practically ice-free Arctic Ocean in late summer will be punctuated by rapid ice loss events (RILEs), i.e., year-to-year reductions in total sea ice extent that occur at a much faster rate than expected from the forced contribution. The extreme sea ice loss associated with RILEs in climate models exceeds any observed rates of sea ice loss since the start of the satellite era, including the highest observed rate of -0.28×106<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="59pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="ff2bafe87f41157e3c794908fc84c03f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-19-3259-2025-ie00002.svg" width="59pt" height="14pt" src="tc-19-3259-2025-ie00002.png"/></svg:svg> km2 yr−1 during 2001–2008. As such, there could be a much faster transition toward practically ice-free conditions than expected based on a linear trend of past observations. However, RILEs are not well understood, and it is currently impossible to predict their occurrence a season to several years ahead. It is therefore essential to improve our understanding of these events. This study presents the first comprehensive analysis of RILEs in a diverse set of 26 CMIP6 models, including five large ensembles, following both low- and high-warming scenarios over the period from 1970 to 2100. Our analysis shows that RILEs are expected to occur year-round, but the timing and duration of these events are found to be season-dependent, with less frequent but longer-lived RILEs in winter and spring and more frequent but shorter-lived RILEs in summer and fall under a high-emission scenario. In addition, we find that the warming scenario has a greater influence on RILE characteristics in the winter–spring season than in the summer–fall season. Our results also emphasize that model uncertainty is larger regarding the probability and characteristics of RILEs for winter–spring events compared to summer–fall ones. Finally, while the initial sea ice extent at which RILEs are triggered depends on whether they occur in September or March, the initial sea ice volume is similar for both months, which emphasizes the critical role of sea ice thickness as a preconditioning factor for RILEs. Based on CMIP6 models, there is an approximately 60 % chance that at least one summer RILE will start in September before 2030. This study of RILEs is particularly opportune as CMIP6 models suggest that, following a period of relative stability in Arctic sea ice, the probability of a rapid sea ice reduction will increase. Given the relatively stable conditions observed between 2015 and 2024, the current summer Arctic sea ice state may have an increased probability of being on the verge of a rapid sea ice loss event.